Need of State-led Strategy for Economic Development in Nepal - Nepal, Purushotam; Chaudhary, Niresh (Koshi Pravah: Multidisciplinary Peer Reviewed Journal, 2023)
The purpose of this study is to explore the way and importance of state-led strategical development in the context of Nepal. Basically, there are three different methods of development strategies that are commonly practiced in the countries of the world. They are state-led strategy, individual-led strategy, and NGO-led strategy of the economic development. Among them, the basic way of development is the investment through the government fund. To find which of these strategies is appropriate in context of Nepal, this review study was conducted. It has also used the simple statistical method of analysis with the help of the secondary data. The findings are presented in table and bar graph. The result of this analysis shows that the most appropriate development strategy is the investment through government organization especially in the initial phase of development of a country. So, it can be suggested that the state-led-strategy of development can be adopted for economic development of Nepal.